Life-space assessment and associated clinical factors: SABE Colombia - Elly Morros-González; Isabel Márquez; José Pablo Prada; Daniela Patino-Hernandez; Diego Chavarro-Carvajal; Carlos Cano-Gutiérrez (Brazilian Society of Geriatrics and Gerontology, 2022)
OBJECTIVES: Our aim was to assess whether an association exists between chronic diseases or multimorbidity and limited life space in older adults. METHODS: This is a secondary analysis of the SABE (Salud, Bienestar y Envejecimiento) Colombia Study. We assessed chronic diseases through self-report, and a limited life space was defined as any score = 60 in the Life-Space Assessment scale. Multimorbidity was defined as having two or more coexisting diseases. We performed bivariate analyses and multivariate logistic regressions aiming to obtain odds ratios with 95% confidence intervals. RESULTS: The prevalence of limited life space was 2.95% with a mean score of 76.27 ± 19.34. Statistically significant associations were found between limited life space and mental disease (OR 1.45; 95%CI 1.15 - 1.82) and between limited life space and multimorbidity (OR 1.32; 95%CI 1.06 - 1.63). CONCLUSIONS: Mental disease and multimorbidity are associated with limited life space in older adults. Therefore, preventing, diagnosing, and treating mental illness should be sought in addition to the existing preventive and therapeutic approaches available for noncommunicable diseases.